An “open” form in art: a phenomenological, communicative, textual aspects - Vyacheslavova, Elena (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2016)
The article is devoted to the problem of “open” forms, the experience of conceptualization of this problem was carried out in Russian aesthetics. The author identifies the discussion points that contains Russian aesthetic concept that aims to substantiate the unity of the ontological foundations of classical art and current art practices. It is shown that in the considered theory the theoretical model of “open” artworks by U. Eco was reinterpreted in the phenomenological aspect based on the aesthetics of R. Ingarden. It is noted, that during this conceptualization the russian author provides a number of theoretical transformations that result in the reduction of artistic forms, deontologisation of artwork, the limitation of the “openness” of artwork by receptive level. The researcher indicates the incompleteness of the received interpretation of “open” form and referring to the phenomenology of text, semiotic and rhetorical theories of the text, justifies the presence in the structure of the artworks of three levels of “openness”, including “openness” as an immanent feature of the artistic form and the “openness” of an artwork to the space of intertextuality. Based on the specifics of fine art, the author considers the methodological position of “dual-view”, providing the status of a work as the modus of ideality, and in the modus of reality. The mechanism of “dual view” is controlled by attentionality. The attentionall structure of the work is the basis of “openness” as the inherent characteristics of the artistic form. The author comes to the conclusion that the approval of the phenomenology of the text and the communicative approach provides the methodological background for the analysis of “open” form as a field of realization of rhetorical structures